Determination of Mapping Relation between Wheel Polygonalisation and Wheel/Rail Contact Force for Railway Freight Wagon Using Dynamic Simulation - Jian Mu; Jing Zeng; Qunsheng Wang; Hutang Sang (Shock and Vibration)
The polygonal wear around the wheel circumference could pose highly adverse influences on the wheel/rail interactions and thereby the performance of the vehicle system. In this study, the effects of wheel polygonalisation on the dynamic responses of a freight wagon are investigated through development and simulations of a comprehensive coupled vehicle-track dynamic model. The model integrates flexible ballasted track and wheelsets subsystem models so as to account for elastic deformations caused by impact loads induced by the wheel polygonalisation. Subsequently, the vehicles with low-order polygonal wear, whether in empty or loaded conditions, are simulated at different speeds considering different amplitudes and harmonic orders of the wheel polygonalisation and thus the mapping relation between wheel/rail impact force and wheel polygonalisation is obtained. The results reveal that the low-order wheel polygonalisation except 1st order and 3rd order can give rise to high-frequency impact loads at the wheel/rail interface and excite 1st-bend modes of the wheelset and “P2 resonance” leading to high-magnitude wheel/rail contact force at the corresponding speed.